Hanoi - Le village du Kinh-Luoc (tan p) - Auteur inconnu (Wikimedia Commons, 1945)
Notice image issue de Wikimedia Commons pour la dmo du fonds documentaire. Titre: Hanoi - Le village du Kinh-Luoc (tan p). A postcard depicting the tomb of the Nguy?n Dynasty Mandarin (and the Viceroy of Tonkin) Hong Cao Kh?i in the city of Hanoi, in the French protectorate of Tonkin.
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale; Carte postale